Robustness of recurrence for a class of stochastic hybrid systems*. Issue 27 (2015) - Subbaraman, Anantharaman; Teel, Andrew R.
Abstract: We study a weak stability property called recurrence for a class of stochastic hybrid systems. Robustness of the recurrence property to various state-dependent perturbations is established under mild regularity conditions for the stochastic hybrid system. A potential application of the robustness results in the development of converse Lyapunov theorems is also outlined.